2017
DOI: 10.1093/ehjci/jex312
|View full text |Cite
|
Sign up to set email alerts
|

Applications of cardiac computed tomography in electrophysiology intervention

Abstract: Cardiac electrophysiology is an evolving specialty that has seen rapid advances in recent years. Concurrently, there has been much progress in the field of cardiac imaging. Electrophysiologists are increasingly requesting cross-sectional imaging in advance of many procedures. Pulmonary vein isolation and left atrial appendage (LAA) occlusion are now an established treatment options for atrial fibrillation. In patients undergoing pulmonary vein isolation, applications of computed tomography (CT) include evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The integration of 3D CT-derived cardiac images into electro-anatomical maps (EAM) allows ablation procedures designed specifically to patient anatomy 123 . Furthermore, CCT is routinely used to assess postprocedural complications, such as esophageal injury and pulmonary vein stenosis 124 . In patients with atrial fibrillation, CCT has been proposed as an alternative to transesophageal echocardiography to exclude left atrium and LAA thrombosis, using dual phase CCT acquisition to avoid false-positive findings 125,126 .…”
Section: Cardiac Computed Tomography Electrophysiological Applicationsmentioning
confidence: 99%
“…The integration of 3D CT-derived cardiac images into electro-anatomical maps (EAM) allows ablation procedures designed specifically to patient anatomy 123 . Furthermore, CCT is routinely used to assess postprocedural complications, such as esophageal injury and pulmonary vein stenosis 124 . In patients with atrial fibrillation, CCT has been proposed as an alternative to transesophageal echocardiography to exclude left atrium and LAA thrombosis, using dual phase CCT acquisition to avoid false-positive findings 125,126 .…”
Section: Cardiac Computed Tomography Electrophysiological Applicationsmentioning
confidence: 99%
“…38 Important aspects of CT evaluation for PV stenosis include comparison to preprocedural anatomy if available as well as consistency within acquisition during the cardiac cycle due to ostial dimension variation. 29 Treatment options for pulmonary vein stenosis after ablation include stenting and balloon dilatation. 39,40 Cardiac CT plays a key role in the intra- and postprocedural evaluation of PVI and remains an informative modality in the evaluation for complications.…”
Section: Pulmonary Vein Isolation Postprocedural Imagingmentioning
confidence: 99%
“…Indeed, intraprocedural fusion imaging technology allows overlay of a 3D reconstruction of the pulmonary veins with electro-anatomic maps and fluoroscopy to better visualize and characterize real-time catheter positioning and application of radiofrequency energy. 29 Studies have suggested that these fusion maps may reduce procedure time, radiation exposure and result in less recurrence rates. 29 Of note, diabetic or obese patients are considered at high risk of early recurrence of atrial fibrillation after PVI.…”
Section: Pulmonary Vein Isolation Intraprocedural Imaging Ct Intrapro...mentioning
confidence: 99%
“…Preprocedural imaging involves evaluation of the number and location of the PVs, relative ostial dimensions which may guide catheter sizing, LA dimensions and morphology, exclusion of left atrial and appendage thrombus, pulmonary venous anomalies, as well as the orientation of the interatrial septum and relative position of the esophagus. 67 The most common variant for example is the drainage of the right middle lobe PV, which typically drains into the right superior PV (in 53%-69% of the population), or directly into the LA with a separate ostium in 17% to 23% of the population. 68,69 Furthermore, the left-sided veins may share a common ostium (6%-35%), resulting in a broad veno-atrial junction, and being a consistent ectopic foci requires preprocedural awareness.…”
Section: Pvi Assessmentmentioning
confidence: 99%